2008
DOI: 10.1080/10402000701739305
|View full text |Cite
|
Sign up to set email alerts
|

Couple Stress Effects on the Dynamic Behavior of Connecting Rod Bearings in Both Gasoline and Diesel Engines

Abstract: An isothermal hydrodynamic analysis of big end connecting rod bearings for both diesel and gasoline engines lubricated with couple stress fluids is undertaken. Based on the V. K. Stokes micro-continuum theory, an incompressible modified Reynolds equation is derived from the fluid motion and mass conservation equations using the assumptions of thin-film theory. The hydrodynamic performance and the crank pin center trajectories are determined numerically by means of the Booker mobility technique. Compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
12
0
4
Order By: Relevance
“…In these circumstances, the destructive metal-to-metal contact between the shaft and bearing surfaces may also be avoided because of the elasticity of the bearing. Qualitatively, these results agree very well with those obtained by the same authors [33] in the case of internal combustion engine connecting-rod bearings lubricated with an iso-viscous polar fluid. As shown in Figure 4, the steps of the computation procedure may be summarized as follows:…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In these circumstances, the destructive metal-to-metal contact between the shaft and bearing surfaces may also be avoided because of the elasticity of the bearing. Qualitatively, these results agree very well with those obtained by the same authors [33] in the case of internal combustion engine connecting-rod bearings lubricated with an iso-viscous polar fluid. As shown in Figure 4, the steps of the computation procedure may be summarized as follows:…”
Section: Discussionsupporting
confidence: 82%
“…The new material constant  is responsible for couple-stress property. In the literature, the effects of couple-stresses on the behavior of journal bearings are studied by defining the dimensionless Owing to its relative mathematical simplicity, the couple-stress fluid model has been widely applied to analyze various hydrodynamic lubrication problems: hydrostatic thrust bearings, slider bearings, rolling bearings, squeeze film bearings, layered journal bearings, and dynamically loaded engine journal bearings [27][28][29][30][31][32][33]. The theoretical results obtained showed that the presence of the couple-stress provides an enhancement in the load carrying capacity, improve the dynamic performance characteristics and the stability of journal bearings, and lengthens the response time of the squeeze film action of the system as compared to the Newtonian lubricant case.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Elsharkawy [23] was interested in the static performance of a compliant bearing lubricated by a polar fluid. More recently still, Lahmar and Bou-Saïd [24] study different types of unsteady loading in a connecting-rod bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Ce type de fluide est caractérisé par deux constantes physiques qui sont la viscosité dynamique du lubrifiant (μ) et une deuxième caractéristique responsable du couple de contrainte dans le fluide (η). Les effets de la rhéologie ou des couples de contrainte sur le comportement du patin serontétudiés en définissant le paramètre de couple de contrainte ( = η/μ) qui représente physiquement la longueur de la chaîne moléculaire des additifs incorporés a l'huile de base tels que les polymères améliorant l'indice de viscosité.À cause de sa simplicité mathématique, le modèle de fluideà couple de contrainte aété largement utilisé dans lesétudes de simulation en lubrification hydrodynamique, hydrostatique,élasto-hydrodynamique et thermo-élasto-hydrodynamique [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Méthode D'homogénéisationunclassified